1995
DOI: 10.1002/prot.340220303
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for serpin inhibitor activity

Abstract: The mechanism of formation and the structures of serpin-inhibitor complexes are not completely understood, despite detailed knowledge of the structures of a number of cleaved and uncleaved inhibitor, noninhibitor, and latent serpins. It has been proposed from comparison of inhibitor and noninhibitor serpins in the cleaved and uncleaved forms that insertion of strand s4A into preexisting beta-sheet A is a requirement for serpin inhibitor activity. We have investigated the role of this strand in formation of ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
149
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(165 citation statements)
references
References 90 publications
14
149
1
1
Order By: Relevance
“…Some authors have concluded that this may represent the results of serpins acting as mechanism-based inactivators (Patston et al, 1991;Gettins et al, 1992;Lawrence et al, 1995). In this case, Met 358-Ser 359 cleavage would be an absolute requirement for inhibition and the inhibited proteinase would exist with its catalytic serine acylated by the a-carbonyl of Met 358 (Lawrence et al, 1995;Wright & Scarsdale, 1995). Others have concluded that cleavage may be a result of the denaturing conditions required to visualize it and that the observed acylation (SDS-stable complex formation) is an artifact and equivalent to a trapped intermediate in the substrate hydrolysis pathway (Travis & Salvesen, 1983;Longstaff &Gaffney, 1991;Mast et al, 1991;Stein & Carrell, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have concluded that this may represent the results of serpins acting as mechanism-based inactivators (Patston et al, 1991;Gettins et al, 1992;Lawrence et al, 1995). In this case, Met 358-Ser 359 cleavage would be an absolute requirement for inhibition and the inhibited proteinase would exist with its catalytic serine acylated by the a-carbonyl of Met 358 (Lawrence et al, 1995;Wright & Scarsdale, 1995). Others have concluded that cleavage may be a result of the denaturing conditions required to visualize it and that the observed acylation (SDS-stable complex formation) is an artifact and equivalent to a trapped intermediate in the substrate hydrolysis pathway (Travis & Salvesen, 1983;Longstaff &Gaffney, 1991;Mast et al, 1991;Stein & Carrell, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, considerable adaptation to the proteinase's substrate cleft may occur during complex formationsetting the serpins apart from the other serine proteinase inhibitor families. Structural and kinetic data have led some workers to propose very different inhibitory mechanisms that often include a requirement for peptide bond scission in serpins, at the P,-PI' bond, not seen in the standard mechanism inhibitors (reviewed by Wright & Scarsdale, 1995).…”
mentioning
confidence: 99%
“…BSZx retained nearly full activity after preincubation with 8E8 in excess and, presumably, the epitope recognized by 8E8 is not located in the loop region. More likely, partial or complete loop insertion caused by complex formation or cleavage results in a structural rearrangement disrupting the epitope [19][20][21]. This suggestion is Min Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Hence, serpin inhibition essentially involves kinetic trapping of the protease in a stable, covalent complex that normally represents a short lived intermediate stage of the protease-substrate reaction (Hermans et al 1995;Patston et al 1991;Cooperman et al 1993;Wright & Scarsdale 1995;Stratikos & Gettins 1999). Partitioning between the substrate or inhibitory pathways is determined by the kinetics of structural changes in the serpin following cleavage of the Pl-Pl' bond (Gettins etal.…”
Section: Serpin Inhibitory Mechanismmentioning
confidence: 99%
“…As the serpin-protease complex has not yet been crystallised, the exact nature of the interaction between serpins and their target proteases has not been directly observed (refer section 1.2.5). However, several recen studies have given valuable insights into the structure of the stable complex and along with numerous kinetic studies of the serpin-protease reaction, have provided the basis for a detailed model of the serpin inhibitory mechanism (Wright & Scarsdale 1995;Gettins et al 1996;Stratikos & Gettins 1999), as detailed below (Figure 1.4). Figure 1.4 Branched p a t h w a y m e c h a n i s m of serpin action s h o w i n g possible structures of intermediates a n d products.…”
Section: Serpin Inhibitory Mechanismmentioning
confidence: 99%